2018
DOI: 10.1111/aos.13832
|View full text |Cite
|
Sign up to set email alerts
|

Nonarteritic anterior ischaemic optic neuropathy and its association with obstructive sleep apnoea: a health insurance database study

Abstract: There was a strong association between NAION and OSA, and the patients with OSA had a higher risk of NAION. Further large-scale, prospective studies are warranted to evaluate the effect of OSA on developing NAION.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…A sleep study later on revealed an undiagnosed severe OSA. This case is an example to support the idea of recent literature that OSA is a strong risk factor for NAION 2 3 5 12–14…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…A sleep study later on revealed an undiagnosed severe OSA. This case is an example to support the idea of recent literature that OSA is a strong risk factor for NAION 2 3 5 12–14…”
Section: Discussionsupporting
confidence: 78%
“…Numerous studies have suggested the association between NAION and OSA by evaluating the prevalence of OSA in NAION patients and vice versa 2 3 5 12–14. The prevalence of OSA in NAION patients was reported to be 71% (12 of 17 cases) by Mojon et al 2 and 89% (24 of 27 cases) by Palombi et al 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ein Beginn der atrophen Veränderungen ist bereits nach ca. 4 Risikofaktoren: arterielle Hypertonie, Diabetes mellitus, Hypercholesterinämie, Sehnervendrusen, kleine Papille ("crowded disc") [2,11], Alter [3], Herz-oder Wirbelsäulenchirurgie [12], Schlafapnoe [13,14], Gerinnungsstörungen [15] Art des Zelltods (Verhältnis von Nekrose/Apoptose)…”
Section: Pupillenreaktion Funduskopie Und Optische Kohärenztomografiunclassified